2014
DOI: 10.15446/agron.colomb.v32n2.42640
|View full text |Cite
|
Sign up to set email alerts
|

Growth analysis in chard plants (Beta vulgaris L. Cicla, cv. 'Pencas Blancas') exposed to different light quality

Abstract: To determine the effects of light quality on the growth indices of plants, Pencas Blancas cultivar chard plantlets were grown for 2 months under five different light treatments, obtained by filtering sunlight through colored polyethylene films. The treatments included: red, blue, green, yellow and transparent cover colors. A transparent cover (white light) was used as the control. The colored covers affected the plant growth. The plants grown under the yellow cover presented a better behavior with regards to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The red light (600–699 nm) and far-red light (700–780 nm), 16 h day photoperiod, 85 μmol m –2 s –1 photosynthetic photon flux density induced better growth in water melon . The combination of 630 nm red light + 660 nm red light + 450 nm blue light + 460 nm blue light improved morphological and physiological activities in melon with 12 h photoperiod under plastic house …”
Section: Daily Light and Light Spectrum Requirements Of Leds In Crop ...mentioning
confidence: 98%
See 1 more Smart Citation
“…The red light (600–699 nm) and far-red light (700–780 nm), 16 h day photoperiod, 85 μmol m –2 s –1 photosynthetic photon flux density induced better growth in water melon . The combination of 630 nm red light + 660 nm red light + 450 nm blue light + 460 nm blue light improved morphological and physiological activities in melon with 12 h photoperiod under plastic house …”
Section: Daily Light and Light Spectrum Requirements Of Leds In Crop ...mentioning
confidence: 98%
“…42 The combination of 630 nm red light + 660 nm red light + 450 nm blue light + 460 nm blue light improved morphological and physiological activities in melon with 12 h photoperiod under plastic house. 43 Light Requirements in Ornamental Crops. The combination of red light + blue light (460−660 nm), blue light + white light (400−500 nm), 16 h/8 h day photoperiod, 50 μmol m −2 s −1 PPFD induced morphological growth in cuttings of chrysanthemum propagated under controlled environment growth room.…”
Section: Requirements Of Leds In Crop Growthmentioning
confidence: 99%
“…With an aim of explaining the influence of regional weather conditions on strawberries, several studies have been carried out [29][30][31]. Some of these studies have shown a critical correlation between strawberry yield and temperature changes [29,30,32].…”
Section: Introductionmentioning
confidence: 99%
“…In the food industry, titratable acidity, colour, electrical conductivity, firmness, pH, and total soluble solids are considered key indicators defining the quality of tomato fruits. Tomato fruit quality tends to improve in protected agricultural systems as compared to open-air systems, hence various production systems in greenhouses have been implemented, including hydroponics and fertigation, chemical and organic fertilization, and biostimulation by using beneficial elements (Casierra-Posada and Aguilar-Avendaño, 2008;García-Sahagún et al, 2009). Although beneficial elements are not essential for plants, they can stimulate positive responses in certain metabolic processes when applied at low dosages (Trejo-Téllez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%